Rapid and accurate diagnosis of hemoglobinopathy and β-thalassemia by ultrahigh-resolution mass spectrometry and tandem mass spectrometry from blood: review of a benchmark study - Prokai, Laszlo (Annals of Translational Medicine, 2019)
Many point mutations of the human hemoglobin (Hb) genes have been documented (1-4) and, without a doubt, more remain to be identified. Most of the mutations are single base replacements in the genes and, thus, result in single amino acid substitutions in the corresponding globin chains.